PENGEMBANGAN E-BOOK BERBASIS HEYZINE FLIPBOOK "WASIBASUL" TENTANG SIFAT WAJIB BAGI RASUL PADA PEMBELAJARAN PAI KELAS 2 SD - Wahyudi, Ghina Aulia Rohmah; Desviana, Sita; Shafarina, Raisha Gysella; Aeni, Ani Nur (Kaisa: Jurnal Pendidikan dan Pembelajaran, 2025)
This research aims to develop an e-book based on the Heyzine Flipbook called “WASIBASUL” (Insight into the Obligatory Nature for the Prophet) as an interactive learning medium for Islamic Religious Education (PAI) subjects in grade 2 of elementary school. This e-book is designed to increase students’ interest and motivation to learn through multimedia features, such as audio, video, images, inspirational stories, and interactive quizzes. This research uses the ADDIE (Analyze, Design, Develop, Implement, Evaluate) development model, which involves analyzing student needs, designing e-book content, developing using digital platforms, such as Canva and Heyzine Flipbook, as well as implementation and evaluation of products. The results of validation by media and material experts, and student questionnaires show that this e-book “WASIBASUL” is very feasible and shows at 95% - 100 % in all indicators. The implementation at SD Negeri Cilangkap II, shows that this e-book can be said to be said to be effective in increasing student involvement and understanding of the material that is mandatory for the Prophet. This research contributes to digital- based learning media innovations that are very relevant to the current technological era, as well as supporting digital literacy in education.